(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article discusses the main directions of improving the quality of higher education. The processes of globalization in the world and the existing environment of deep competition between companies require professionals to be prepared for this. They not only provide favorable conditions for the developmentof their ideas and the implementation of the created theoretical models, but also are an important intellectual factor for the innovative development of the economy. Today, in the era of development of high technologies and information processes in the world, the competition between companies for the training of highly qualified specialists has increased.